Working in group therapy during a period of social trauma. (June 2019) - Mitsopoulou-Sonta, Lila
My experience in working with groups in therapy shows that the individual is inevitably bound to the social. Based on a group of borderline and psychotic patients in a psychiatric hospital, I would like to demonstrate the effects of social trauma (terrorist attack) on the internal life of the group, as well as the different types of transference that we observe in it. The group works with the 'Photolanguage' method. Patients have the possibility to put words on their affects, speak about memories and sensations through images that mobilize feelings in a playful manner. The capacity of the group to contain and to transform is precious and promotes the subjective appropriation of difficult affects. Group therapy is important in this type of situation as the diffusion of transference reinforces the capacity of contention in the group. The synergy between the group dynamics and the mediating object offers a field of work on the primitive experiences of each patient and creates a transformation of internal images and representations as the person works on the 'first psychic material', which is not elaborated.